1992
DOI: 10.3109/08982109209039903
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Liposomal Doxorubicin for Human Use

Abstract: A liposome-associated doxorubicin formulation that has been utilized in two phase Iclinical trials at two separate medical centers is described. This work deals with formulation optimization, process development, quality control assays on raw materials, characterization assays for these liposomes, and their short-term stability. One of the main goals of this work is to provide a model for the production of liposomal formulations of sufficient quantity and quality to be used in clinical trials.Vials containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The level of DXR aglycone in the L-DXR clinical batches was minimal (less than 0.3%) and the overall recovery of the parent drug was high (above 95%); however, some 9-carboxy doxorubicin (-5%) was detected. 36 Results obtained by the two assays for lipid peroxidation described above showed no increase in the level of conjugated dienes or changes in fatty acid composition of L-DXR phospholipids when compared to the lipid raw materials, both during vesicle preparation and storage of the L-DXR when desferal and a-tocopherol succinate were present in the formulation (Table V) absence, the level of conjugated dienes was consistently higher. It varied from one preparation to the other, reaching levels as high as 4 mol % .…”
Section: A Chemical Stabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…The level of DXR aglycone in the L-DXR clinical batches was minimal (less than 0.3%) and the overall recovery of the parent drug was high (above 95%); however, some 9-carboxy doxorubicin (-5%) was detected. 36 Results obtained by the two assays for lipid peroxidation described above showed no increase in the level of conjugated dienes or changes in fatty acid composition of L-DXR phospholipids when compared to the lipid raw materials, both during vesicle preparation and storage of the L-DXR when desferal and a-tocopherol succinate were present in the formulation (Table V) absence, the level of conjugated dienes was consistently higher. It varied from one preparation to the other, reaching levels as high as 4 mol % .…”
Section: A Chemical Stabilitymentioning
confidence: 84%
“…A formulation of L-DXR was developed in our laboratories through all the stages described in Fig. 1, including formulation optimization, upscaling, phase I clinical trials, and pharmacokinetic studies.22, 23,32,34- 36 The drug development stages will be only briefly reviewed here.…”
Section: Development Of Liposomes As Drug Carriermentioning
confidence: 99%
“…These parameters are comparable to those previously obtained with phospholipid-based liposomes. [48][49][50] It should be pointed out that the reported trapping efficiency was very good since the drug to lipid ratio is expressed in molar terms and the investigated liposomes were formed from a single-chain amphiphile, in contrast to phospholipids, which bear two hydrophobic chains.…”
Section: Dox Active Loading and Releasementioning
confidence: 99%
“…Briefly, it consisted of egg phosphatidylcholine (PC), phosphatidylglycerol (PG), cholesterol, and D-alpha tocopherol succinate at a molar ratio of 7: 3: 4: 0.2, respectively. Quality control analysis was done as previously reported (Amselem et al, 1990b(Amselem et al, , 1991. Most of the entrapped ADM was present in the liposome bilayer (<90%).…”
Section: Liposome Formulationmentioning
confidence: 99%
“…ADM and its metabolites were extracted as described by Andrews et al (1980). HPLC analysis of ADM and metabolites was done following the procedure of Beijnen et al (1985) with minor modifications as previously reported (Amselem et al, 1991). A reverse phase column (RP-C8, Alltech, Deerfields, IL) measuring 150 x 4.6 mm was used.…”
Section: Liposome Formulationmentioning
confidence: 99%